Developing Public-Private Partnership Initiatives in the Middle East and North Africa : From Public Debt to Maximizing Finance for Development - Arezki, Rabah; Belhaj, Ferid (World Bank, Washington, DC, 2019)
This paper argues for a novel approach to financing infrastructure needs in Arab countries. It first describes the context of rising public debt in the region, contrasting it with the vast infrastructure needs. It then discusses the challenges in meeting these needs with traditional financing. The paper then makes the case for maximizing finance for development, by using public-private partnerships, and presents a few successful examples in Arab countries. Finally, the paper explores the way forward and concludes on the need for strong state capacity and integrity to promote the maximizing finance for development approach.